2014
DOI: 10.1186/1753-2000-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Normative data and psychometric properties of the strengths and difficulties questionnaire among Japanese school-aged children

Abstract: BackgroundAlthough child mental health problems are among the most important worldwide issues, development of culturally acceptable mental health services to serve the clinical needs of children and their families is especially lacking in regions outside Europe and North America. The Strengths and Difficulties Questionnaire (SDQ), which was developed in the United Kingdom and is now one of the most widely used measurement tools for screening child psychiatric symptoms, has been translated into Japanese, but cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
99
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 37 publications
18
99
2
7
Order By: Relevance
“…Internal reliability for the SDQ subscales varied from good to very low reliability: emotional symptoms (α = .70), conduct problems (α = .53), hyperactivity/inattention (α = .47), peer relationship problems (α = .26), and prosocial behavior (α = .61). The range of internal reliability estimates is broadly consistent with previous work on the scale (e.g., Colins et al, 2013), and the particularly low internal reliability for the conduct problems and peer relationship problems is consistent with youth samples in Japan (Moriwaki and Kamio, 2014), China (Mellor et al, 2011), and multicultural samples in the Netherlands (Colins et al, 2013; Mieloo et al, 2014). Past work suggests that differences in cultural reports of youth behavior may influence caretaker reports, particular in cross-cultural or minority group samples (Mieloo et al, 2014), thereby influencing reliability estimates.…”
Section: Methodssupporting
confidence: 84%
“…Internal reliability for the SDQ subscales varied from good to very low reliability: emotional symptoms (α = .70), conduct problems (α = .53), hyperactivity/inattention (α = .47), peer relationship problems (α = .26), and prosocial behavior (α = .61). The range of internal reliability estimates is broadly consistent with previous work on the scale (e.g., Colins et al, 2013), and the particularly low internal reliability for the conduct problems and peer relationship problems is consistent with youth samples in Japan (Moriwaki and Kamio, 2014), China (Mellor et al, 2011), and multicultural samples in the Netherlands (Colins et al, 2013; Mieloo et al, 2014). Past work suggests that differences in cultural reports of youth behavior may influence caretaker reports, particular in cross-cultural or minority group samples (Mieloo et al, 2014), thereby influencing reliability estimates.…”
Section: Methodssupporting
confidence: 84%
“…Respondent scores for the Prosocial Scale were also compared with clinical cut-offs 2 derived from British samples: average 6-10 (80% sample); borderline 5 (20%); and clinical 0-4 (10%) (Goodman, 1997). Child self-reports for the Prosocial Scale in this study (ɑ=.89), yielded stronger reliabilities than previous investigations (.69-.82) (Deighton et al, 2014), while results for the carer report (ɑ=.69) were within an accepted range (.63-.85) (Deighton et al, 2014). …”
Section: Methodscontrasting
confidence: 60%
“…However, limitations are noted in the use of a single (5-item) instrument, despite the adequate psychometric properties in this sample. The three-point Likert scale design limits variability in data, and may not be sensitive to detect changes over time (Deighton et al, 2014). Furthermore, cross-sectional studies do not provide a longitudinal perspective on psychosocial adjustment (Sherr at al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…; Matsuishi et al . ; Moriwaki & Kamio ). Previous study of 5 to 10‐year‐old children in UK and of 4 to 6‐year‐old in Japan showed similar total difficulties score to ours, 8.6 and 8.27, respectively (Matsuishi et al .…”
Section: Discussionmentioning
confidence: 98%